The Bow and Cultural Complexity of the Canadian Plains. Issue 3 (17th June 2013) - Walde, Dale
<x xml:space="preserve">Abstract</x> The timing and circumstances of the introduction of the bow and arrow into past North American economic and social lifeways have been sources of interest and controversy among archeologists for a very long time. Initial interpretations of the adoption of the bow and arrow generally seem to have been based on the rather straightforward assumption of functional superiority as a hunting tool. That is, the bow and arrow was simply a better instrument than the atlatl‐dart technology it replaced.12 More recently, however, researchers exploring the effectiveness of the atlatl as a hunting tool have responded with studies that challenge the assumed universal functional superiority of the bow and arrow as a hunting device.345 Social coercion and warfare theory presents an alternative perspective on the adoption of the bow and arrow.